Carbon-11 and Fluorine-18 Labeled Amino Acid Tracers for Positron Emission Tomography Imaging of Tumors - Sun, Aixia; Liu, Xiang; Tang, Ganghua (Frontiers in Chemistry, 2018)
Tumor cells have an increased nutritional demand for amino acids(AAs) to satisfy their rapid proliferation. Positron-emitting nuclide labeled AAs are interesting probes and are of great importance for imaging tumors using positron emission tomography (PET). Carbon-11 and fluorine-18 labeled AAs include the [1-11C] amino acids, labeling alpha-C- amino acids, the branched-chain of amino acids and N-substituted carbon-11 labeled amino acids. These tracers target protein synthesis or amino acid(AA) transport, and their uptake mechanism mainly involves AA transport. AA PET tracers have been widely used in clinical settings to image brain tumors, neuroendocrine tumors, prostate cancer, breast cancer, non–small cell lung cancer (NSCLC) and hepatocellular carcinoma. This review focuses on the fundamental concepts and the uptake mechanism of AAs, AA PET tracers and their clinical applications.